Wrestling with Tradition: Revitalizing the Orkney Chair and Other Culturally Significant Crafts. (2nd September 2017) - Twigger Holroyd, Amy; Cassidy, Tom; Evans, Martyn; Walker, Stuart
Abstract: Across the world, "culturally significant" designs, products, and practices – such as traditional crafts – have been pushed to the margins by the forces of modernization and globalization. Appreciation of the positive attributes of these traditions drives widespread revitalization initiatives, often involving designers. Awareness of the cultural ramifications of design-led revitalization may deter enthusiasm for radical initiatives and instead promote preservation efforts. Yet a deconstruction of the popular understandings of tradition and origin indicates a need for change and cross-cultural contact. This article proposes that social value – central to a traditional craft's cultural significance – should be used to guide revitalization.